Analisis Perilaku Persepsi Pengendara Sepeda Motor Terhadap Keselamatan Berkendara - -, Ammar Fadhil (Jurnal Rekayasa Teknik dan Teknologi, 2024)
People need a mode of transportation to facilitate daily activities, one of the modes of transportation in Aceh is the increase in motorbike ownership. The increase in motorbike ownership is not matched by increased awareness of traffic safety by road users, which will certainly have an impact on increasing the number of accidents. WHO (2018) reports the number of deaths based on road users in Indonesia, 74% of deaths were contributed by motorcyclists. This research aims to identify personal characteristics and unsafe driving behavior on the traffic safety of motorbike users. Research data was collected in Banda Aceh and parts of greater Aceh using the Driving Behavior Inventory (DBI) instrument through an online survey questionnaire approach "self-reporting driving behaviors". The results of research on socio-demographics using cross tabulation show that men aged 20-29 years have more than 6 years of experience with the highest score of having experienced a traffic accident. Perception of the respondent variable Violation (V) on the indicator "driving very close to another vehicle in front" which has the lowest value of 2.91, variable Error (E) on the indicator "maneuvering without turning on the turn signal" which has the second lowest value of 2 .98, variable Driving Safety (DS) in the indicator that has the highest scale value is "be careful in accident-prone places" of 3.66.